A Study Probing for Multiple Intelligences in Secondary School Textbooks of Selected School Subjects in the Present Curriculum - Νταλλή Κλεοπάτρα; Φλουρής Γεώργιος (Education Sciences, 2019)
This study highlights Howard Gardner’s theory which supports the position that intelligence is not of a single type-as measured by the I.Q. test but it is comprised of at least eight relatively different capabilities. Given the formal announcements of the Greek Ministry of education about ‘holistic development of students’ it is expected that curriculum subjects and learning activities in the textbooks will be multi modal so that they will allow teachers to cultivate in students multiple dimensions of cognitive, emotional and social development. Based on the above conceptualization, a content analysis study was conducted in selected curriculum textbooks, at the secondary level, in order to ascertain how "intelligent are the textbooks” under analysis and what varieties of intelligences are reflected in them. To this end, the present study probed for Gardner’s eight types of intelligences in selected school textbooks of secondary education, namely Language arts and history textbooks as well as student books. The analysis at hand revealed that the learning activities of the above textbooks do not lead to multiple intelligences (MI) in order to better tailor to the needs of all students. Additionally, it was found out that only those students who possess the advantage of having fluency in linguistic and logical-mathematical types of intelligences will be able to master the prescribed activities. Another major finding of the study revealed that these two types of intelligences seem to dominate in all school subjects under analysis. Furthermore, the results revealed that the array of MI of the textbooks analyzed is limited, with the exception of linguistic and logical-mathematical intelligences. Similar results were also found in previous curriculum and textbook studies conducted at the elementary level in Greece. It is recommended that a multiplicity of intelligences ought to be cultivated via all school subjects and activities in compulsory education, through the multiple representation of content and appropriate teaching strategies as well as by presenting equally the ‘entry points’ of all intelligences as suggested by the founder of the theory, Howard Gardner.